2020
DOI: 10.1021/acs.inorgchem.0c01618
|View full text |Cite
|
Sign up to set email alerts
|

Oxo-Free Hydrocarbon Oxidation by an Iron(III)-Isoporphyrin Complex

Abstract: Metal-halides that perform proton coupled electrontransfer (PCET) oxidation are an important new class of high-valent oxidant. In investigating metal-dihalides, we reacted [Fe III (Cl)(T-(OMe)PP)] (1, T(OMe)PP = meso-tetra(4-methoxyphenyl)porphyrinyl) with (dichloroiodo)benzene. An Fe III -meso-chloro-isoporphyrin complex [Fe III (Cl) 2 (T(OMe)PP-Cl)] (2) was obtained. 2 was characterized by electronic absorption, 1 H NMR, EPR, and X-ray absorption spectroscopies and mass spectrometry with support from computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 101 publications
2
13
0
Order By: Relevance
“…For an ideal HAT or CPET, a slope of 0.5 would be expected and for a non‐concerted PCET mechanism a slope close to one is expected [31b, 32] . Although the measured slope here is slightly less than the expected 0.5, there have been several reports of similar deviations for a HAT mechanism, and the value is comparable for those obtained for other high‐valent metal–halides [5a,c, 11, 31b, 33] …”
Section: Resultssupporting
confidence: 75%
“…For an ideal HAT or CPET, a slope of 0.5 would be expected and for a non‐concerted PCET mechanism a slope close to one is expected [31b, 32] . Although the measured slope here is slightly less than the expected 0.5, there have been several reports of similar deviations for a HAT mechanism, and the value is comparable for those obtained for other high‐valent metal–halides [5a,c, 11, 31b, 33] …”
Section: Resultssupporting
confidence: 75%
“…[ 31b , 32 ] Although the measured slope here is slightly less than the expected 0.5, there have been several reports of similar deviations for a HAT mechanism, and the value is comparable for those obtained for other high‐valent metal–halides. [ 5a , 5c , 11 , 31b , 33 ]…”
Section: Resultsmentioning
confidence: 99%
“…The oxidative functionalization of inert saturated hydrocarbons remains a challenge. , High-valent metal oxidants are ideal candidates for C–H bond activation via a hydrogen atom transfer (HAT) mechanism. High-valent metal–halides have attracted attention as acting as potent oxidants. We showed that a Ni III –Cl entity performs HAT and postulated that the thermodynamic driving force for HAT was the bond dissociation free energy (BDFE) of the free HCl product . Subsequently, a Ni III –F complex showed 4300-fold enhanced rate constants in the oxidation of xanthene and CHD compared to those of Ni III –Cl, the enhanced reactivity attributed to a stronger H–F bond .…”
Section: Introductionmentioning
confidence: 99%